SUSTAINABILITY ANALYSIS OF ETHANOL LARGE SCALE PRODUCTION NETWORK IN BRAZIL - MOLLO NETO, Mario; VENDRAMETTO, Oduvaldo; WAKER, Robert Ari (Revista Brasileira de Engenharia de Biossistemas, 2010)
With growing interest worldwide in the use of liquid biofuels in the transport sector, ethanol is considered as one of the best alternatives. Rising oil prices, environmental concerns and interests in energy security have driven Brazilian researchers to look to biofuels production as a potential solution. Other driving forces are the need to stabilize commodity prices and cut down on agricultural subsidies. This paper describes the analysis of Brazilian large-scale network of ethanol production and lead to answer issues related to the sustainable development indicators by studying the structural characteristics of the production chain through social network analysis (SNA). The result showed two structural indicators that monitor the growth of the production chain and also indicates sustainability, based on the fact that no major change occurred in the area planted with sugarcane. The increasing power of distributors is noticed by the increase of the degree of centrality and the strengthening of the chain which is visible through the density evolution.